SHOPPING MOTIVATION IN MEDIATING THE INFLUENCE OF DIGITALIZATION AND BANKING TRANSACTION PROTECTION ON ONLINE SHOPPING DECISIONS - Qurba, Ulul; Rafika, Lailatul; Miranti, Titis (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2022)
Since the digitalization of banking, consumer shopping decisions have changed. Moreover, consumers also need to re-examine transaction protection in the digitalization era. This study wants to review the effect of digitalization and the protection of banking transactions on online shopping decisions by adding shopping motivation as a mediating variable. Researchers used primary data from 150 respondents in Malang City. Structural Equation Modelling (SEM) with Partial Least Square (PLS) approach was used to analyze the data. The results showed that transaction digitization, transaction protection, and shopping motivation positively and significantly affected shopping decisions. Moreover, shopping motivation can mediate the effect of digitization and transaction protection on shopping decisions. Furthermore, the efforts of related parties to increase consumer spending motivation also need to be improved. If it is carried out sustainably, it is not inevitable that this will enhance the country's economy.